The Effective Invitation A practical guide for the pastor - Streett, R. Alan (Grand Rapids, Mich. Kregel Publications, 2004)
Is the public invitation to accept Christ a vital part of your preaching ministry? Dr. R. Alan Streett provides practical and biblical models to revitalize the "altar call" in this expanded second edition of The Effective Invitation. Dr. Streett traces th
Keywords: Evangelistic invitations